Respuestas

¡La mejor respuesta!
2012-07-20T19:32:28+02:00

1..

-[-8a-{2b+[-5a+(3a-2b)-(-4a+5b)]+7b}+2a]=

-[-8a-{2b+[-5a+3a-2b+4a-5b)]+7b}+2a]=

-[-8a-{2b+[-5a+3a+4a-2b-5b]+7b}+2a]=

-[-8a-{2b+[ 2a -7b ]+7b}+2a]=

-[-8a-{2b+2a -7b+7b}+2a]=

-[-8a-{2b-7b+7b+2a}+2a]=

-[-8a-{2b+2a}+2a]=

-[-8a-2b-2a+2a]=

-[-8a-2a+2a-2b]=

-[-8a-2b]=

= 8a+2b

 

2..

x-[5+3x-{6x-(7+x)}-9]=

x-[5+3x-{6x-7-x}-9]=

x-[5+3x-{6x-x-7}-9]=

x-[5+3x-{5x-7}-9]=

x-[5+3x-5x+7-9]=

x-[3x-5x+7+5-9]=

x-[-2x+3]=

x+2x-3=

=3x-3

 

*Espero haberte ayudado, saludos.

2012-07-20T19:35:11+02:00

-[-8a-{2b+[-5a+(3a-2b)-(-4a+5b)]+7b}+2a]=

-[-8a-{2b+[-5a+3a-2b+4a-5b]+7b}+2a]=-[-8a-{2b+[2a-7b]+7b}+2a]=

= -[-8a-{2b+[2a-7b]+7b}+2a]=-[-8a-{2b+2a-7b+7b}+2a]=

=-[-8a-{2b+2a}+2a]=-[-8a-2b-2a+2a]=-[-8a-2b]=8a+2b

 

 

x-[5+3x-{6x-(7+x)}-9] = x-[5+3x-{6x-7-x}-9] = x-[5+3x-{5x-7}-9] =

= x-[5+3x-5x+7-9] = x-[3-2x] = x-3+2x = 3x-3